Revisiting the nature of Cu sites in the activated Cu-SSZ-13 catalyst for SCR reaction. Issue 1 (6th November 2014) - Borfecchia, E.; Lomachenko, K. A.; Giordanino, F.; Falsig, H.; Beato, P.; Soldatov, A. V.; Bordiga, S.; Lamberti, C.
Abstract : X-ray absorption and emission spectroscopy, FTIR and DFT unravel the major Cu species in the activated Cu-SSZ-13 catalyst for NH3 -SCR. Abstract : Cu-SSZ-13 is a highly active NH3 -SCR catalyst for the abatement of harmful nitrogen oxides (NO x, x = 1, 2) from the exhausts of lean-burn engines. The study of Cu-speciation occurring upon thermal dehydration is a key step for the understanding of the enhanced catalytic properties of this material and for identifying the SCR active sites and their redox capability. Herein, we combined FTIR, X-ray absorption (XAS) and emission (XES) spectroscopies with DFT computational analysis to elucidate the nature and location of the most abundant Cu sites in the activated catalyst. Different Cu species have been found to be dominant as a function of the dehydration temperature and conditions. Data analysis revealed that the dehydration process of Cu cations is essentially completed at 250 °C, with the formation of dehydrated [CuOH] + species hosted in close proximity to 1-Al sites in both d6r and 8r units of the SSZ-13 matrix. These species persist at higher temperatures only if a certain amount of O2 is present in the gas feed, while under inert conditions they undergo virtually total "self-reduction" as a consequence of an OH extra-ligand loss, resulting in bi-coordinated bare Cu + cations. Synchrotron characterization supported by computational analysis allowed an unprecedented quantitative refinement of the local environment and structural parameters of these Cu(ii ) and Cu(i ) species.